Green tea supplementation prevented oxidative stress, fibrosis, and myocardial damage in isoproterenol-induced Swiss albino mice - Shampa Akter; Shatil Rafia; Raiyana Huda; Rashedul Haque; Sajib Paul; Md.Tipu Sultan; Md. Kawser; Faizul Islam Chowdhury (Elsevier, 2024)
Introduction: One of the main causes of death and morbidity in people with cardiovascular disorders is myocardial infarction. This study investigated the impact of green tea (GT) leaf powder on isoproterenol (ISO)-induced myocardial infarction in Swiss albino mice. Methods and materials: 4 to 5 weeks male Swiss albino mice were divided into four groups with 6 mice in every group: Control, ISO, Control + GT and ISO+ GT leaves powder. All of the mice were sacrificed at the end of the investigation. Heart organ and blood plasma samples were taken, and they were tested for oxidative stress indicators and several biochemical parameters. To investigate the formation of mononuclear cells and fibrosis in the heart histopathological staining of tissue sections was also carried out. Results: In this experiment, supplementation with green tea leaf powder in ISO-administered mice prevented the increased activity of the AST, ALT, and ALP enzymes. Additionally, three more tests were performed such as CK-MB, Creatinine, and Uric acid whose levels were increased by isoproterenol, and treatment of green tea reduced these elevated levels. Due to the supplementation of green tea leaf powder, ISO-administered mice had lower levels of lipid peroxidation product, nitric oxide, advanced protein oxidation product, and myeloperoxidase. Mice exposed to ISO had considerably higher levels of oxidative stress markers and lower levels of cellular antioxidants including catalase activity, SOD activity, and reduced glutathione concentration. Additionally, the heart of ISO-induced mice revealed substantial fibrosis and inflammatory cell infiltration. Furthermore, green tea leaf powder supplementation prevented inflammatory cell infiltration and fibrosis in ISO-administered mice. Conclusion: In conclusion, the findings imply that supplementing with green tea leaf powder might lower the risk of myocardial infarction in mice given ISO, potentially by reducing oxidative stress, inflammation, and fibrosis.